Personal Selling to Reach Consumers (Case Study at PT. Teknologi Mudah Terhubung) - Bayuputra, Sultan Aulia; Mulyana, Dadan; Suherman, Maman (Green Publisher Indonesia, 2025)
In the rapidly evolving business landscape, Indonesia has emerged as the sixth-largest country in terms of start-up growth. This surge in new enterprises necessitates that companies develop effective and efficient marketing and promotional strategies to remain competitive. Personal selling remains a crucial promotional tool, as demonstrated by PT. Teknologi Mudah Terhubung, which utilizes this method to market its products. This study aims to explore the stages of personal selling, the messaging strategies involved, the challenges faced during the process, and the rationale behind adopting the